The ethical leadership of the secondary and governmental principals in Al- Shoubak Governorate and its relationship with teachers’ performance from their points of view - Almalaheem, Odeh Ibraheem (Journal of Educational and Psychological Sciences, 2020)
The current study aims at investigating the ethical leadership of the secondary and governmental principals in al Shoubak Governorate and its relationship with teachers’ performance from their points of view. A questionnaire has been distributed to 110 respondents. The researcher adopts the descriptive and relational approach as a means to analyze data through adopting and developing Al - shatwi and Al- Habib’s (2017) scales to measure the ethical leadership of the secondary and governmental principals. Besides، Al- awli and Qudah’s (2016) scale has been adopted to measure secondary teachers’ performance. The results show that the total arithmetic mean of the ethical leadership was 3.58 with an intermediate appreciation; whereas، the arithmetic mean of teachers’ performance was totally 3.77 with existing a relational and positive relationship which is statistically significant among the ethical leadership dimensions and job performance dimensions of the governmental principals. The study recommends the government secondary school principals to pay more attention in practicing ethical leadership considerations.
Keywords: Ethical leadership; Job performance